The Influence of Financial Literacy, Type of Job and Good Amil Governance (GAG) on Interest in Zakat, Infaq And Sedekah (ZIS) at The National Zakat Amil Board - Hikmah Endraswati; Fitri Dwi Ristawati; Melis (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
The purposes of this research are to determine the influence of financial literacy, type of work and Good Amil Governance (GAG) on interest in ZIS at BAZNAS Yogyakarta in 2024. The population taken in this research is muzaki who lives in DIY, who has distributed ZIS to BAZNAS DIY in 2024 , and has been registered with the Baznas Management System (SIMBA). The number of samples in this study was 95 respondents. The analysis technique used is multiple regression. The research results showed that financial literacy has a positive effect on interest in ZIS at Baznas DIY, good amil governance has a positive effect on interest in ZIS at Baznas DIY partially and financial literacy, type of work and good amil governance have an effect on interest in ZIS at Baznas DIY. However, the type of work has no effect on ZIS interest in Baznas DIY. The implications of this research are that it is necessary to maintain and improve understanding of financial literacy through academic activities, outreach to the community and improving good amil governance in Baznas DIY through the principles of good amil governance. Keywords: financial literacy, type of work, good amil governance, interest, zakat, infaq, sedekah, Baznas